Poems 1957-2013 - Lehmann, Geoffrey, 1940- (Crawley, Western Australia : UWA Publishing, 2014)
This substantial volume, Poems 1957-2013, contains all of the poetry written by Geoffrey Lehmann considered by the poet to be worthy of inclusion. He has taken the prerogative of the mature artist looking back to revise poems, sometimes substantially, and to restore lines and passages he had removed from earlier versions. Displaying the breadth and depth of his poetry, Lehmann explores human nature in settings as diverse as ancient Rome and rural New South Wales, from searing satire to the domestic life of a family.
Prime Minister's Literary Awards, poetry, winner, 2015.
Keywords: Australian poetry; English poetry -- Australian authors; Australian poetry -- 21st century; Australian poetry -- 20th century; Australian